Innovative Nanomaterial Properties and Applications in Chemistry, Physics, Medicine, or Environment (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
This Special Issue, “Innovative Nanomaterial Properties and Applications in Chemistry, Physics, Medicine, or Environment”, focused on (i) the synthesis and characterization of nanoparticles, nanotubes, nanowires, or nanofibers; (ii) nanostructures (graphene, zeolites, membrane, etc.), coatings, and thin films; (iii) the correlation between the chemical composition, morphology, surface, and magnetic properties of nanostructured materials; (iv) the thermal behaviour of ceramic pigments with applications in glazes; (v) nanomaterials for photocatalysis and electrocatalysis; (vi) nanomaterials for water purification; (vii) nanomaterials for the adsorption of organic and inorganic pollutants; and (viii) nanomaterials for biosensing and biomedical applications. This Special Issue includes 12 original research papers and highlights the development of synthesis and characterization of nanomaterials and nanostructures of different natures with various applications in chemistry, physics, medicine, biology, and the environment.